Development and verification of RP-3 aviation kerosene surrogate fuel models using a genetic algorithm. (15th March 2022) - Yu, Zhiqing; Wei, Shengli; Wu, Chengcheng; Wu, Lirong; Sun, Linxiao; Zhang, Zhicheng
Highlights: Two new surrogate fuel models for RP-3 kerosene were proposed by applying genetic algorithm. A reaction mechanism consisting of 1408 species and 8965 reactions of surrogate model was developed. S1 is closer to the properties of RP-3, whereas S2 is more compatible with fuel in hydrocarbon group composition. For ensure the reliability of the models, physical and chemical validation were performed under widely conditions. Abstract: For emulation of the physicochemical characteristics and hydrogen-carbon group composition of RP-3 aviation kerosene, two models were composed of three components including n-dodecane, n-butylcyclohexane and n-butylbenzene by genetic algorithm optimization methodology with physical properties measurements (S1, 27.9/63.0/9.1 mol%; S2, 58.0/30.0/12.0 mol%). The numerical results of properties using the surrogate fuels were compared with experimental data. Both models had good performance in predicting the physical properties by analyzing the trends of density and kinematic viscosity under different temperature and pressure conditions. Based on the proposed surrogates, a detailed RP-3 surrogate chemical reaction mechanism was developed by decoupling methodology which including 1408 species and 8965 reactions. Autoignition properties, oxidation properties and laminar combustion properties of surrogates were compared with RP-3 experimental data. Two models exhibited good matching on ignition behaviors with RP-3 at high and low temperatures. Moreover, the components proportion difference had a great influence on the ignition properties in the negative temperature coefficient region. It also made the predicted value of the laminar combustion velocity of S1 higher than that of S2.